Efficacy and safety of cryoablation for localized renal tumor as an alternative approach to partial nephrectomy - Barjolle, Irène; Ah-Thiane, Loic; Frampas, Eric; Karam, Georges; Rigaud, Jérôme; David, Arthur (Frontiers in Oncology, 2023)
Renal cryoablation displays a profile of high tolerance, including in a frail population. Cryoablation appears as a validated alternative treatment to surgery for renal tumors smaller than 4 cm. However, evidence is lacking for larger tumors, despite encouraging data for tumors up to 7 cm. Material and methods: This retrospective descriptive study of a population with a stage T1b renal tumor treated by cryoablation was conducted at the Nantes University Hospital between January 2009 and July 2021. Primary endpoint was 3-year rate of local recurrence. Secondary endpoints included technical efficacy, overall and cancer-specific survivals, and safety assessment. Results: 63 patients were analyzed. Three-year rate of local recurrence was 11.1%. Primary and secondary technical efficacies were achieved in 88.9% and 96.8% of patients, respectively, and 3year overall and cancer-specific survival were 87.3% and 95.2%, respectively. Most patients (73%) experienced no complications, 13% of patients had minor (CIRSE grades 1 or 2) adverse effects, and 13% had severe but non-lethal (CIRSE grade 3) adverse effects. One patient died following cryoablation due to colic perforation. The most common AE (all grades) was hemorrhage (9.5%). Discussion: This study showed a good efficacy and safety of cryoablation for renal tumors up to 7 cm (T1b). Our results were consistent with a rather sparse literature, and contributed to guide future recommendations about cryoablation as an alternative to surgery for T1b renal tumors.